Correlation between particle size distribution and explosion intensity of aluminum powder. (December 2022) - Ren, Xiaofeng; Zhang, Jiangshi
Abstract: To successfully reduce the occurrence of aluminum powder explosion accidents, this study uses a statistical analysis approach to examine the relation between 14 particle size parameters ( D 10 – D 90, D 3, 2, D 4, 3, σ D, PSS, and SSA) and 5 explosion intensity parameters ( P max, (dP/dt) max, K st, t 1 min, and t 2 min ). Note that D 10 – D 90 represent the 10th–90th percentiles of particle size distribution, respectively, unit: μm; D 3, 2 is the average diameter of surface area momentum, unit: μm; D 4, 3 represents the average diameter of volume momentum, unit: μm; σ D represents the particle size polydispersity; PSS is the particle size span, unit: μm; and SSA is the specific surface area, unit: m 2 ·kg −1 ; P max is the maximum explosion pressure, unit: MPa; (dP/dt) max is the maximum explosion pressure increase rate with time, unit: MPa·s −1 ; K st is the explosion index, unit: MPa·m·s −1 ; t 1 represents the time from the start of ignition to the time when the maximum pressure is attained in the 20-L explosion sphere cavity, unit:·s, t 2 represents the time from the start of ignition to the time when the explosion pressure increase rate reaches the maximum value, unit:·s. The t 1 min and t 2 min represent the minimum value of t 1 and t 2, respectively, unit:·s. The stepwise regression method is used to screen the effective particle size parameters that can describe the effect of particle size distribution on the explosive intensity of aluminum powder. The results indicate that σ D and PSS are not recommended to characterize the particle size distribution in examining the explosion intensity. In addition, among the particle size percentiles, D 10, D 20, and D 30 have the strongest correlation with the explosion intensity parameters. SSA has a strong correlation with (dP/dt) max and K st, and D 3, 2 has a strong correlation with P max and t 2 min . The correlation of the small particle size percentiles D 10 and D 20 with P max as obtained by the stepwise regression method is statistically significant. Moreover, the correlations of SAA with (dP/dt) max and K st ; D 10, D 3, 2, and D 30 with t 1 min ; and D 10 and SSA with t 2 min are statistically significant. Therefore, it is advised to use particle size percentiles ( D 10 – D 30 ) and D 3, 2 to describe the particle size distribution when examining the explosion intensity. Furthermore, we should focus on the proportion of small-particle-size aluminum powder components ( D 10 – D 30 ). Highlights: The relation between 14 particle size parameters and 5 explosion intensity parameters was analyzed. Effect of different particle size parameters on the explosion intensity of aluminum powder was discussed. The stepwise regression method was used to screen the effective particle size parameters.